1999
DOI: 10.1186/1297-9686-31-3-239
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of milk proteins in African Bos taurus and Bos indicus populations. Characterization of variants αs1-Cn H and κ-Cn J

Abstract: The polymorphism of caseins, a-lactalbumin and β-lactoglobulin was investigated in African Bos taurus (N'Dama, Baoulé, Kuri) and Bos indicus (Shuwa Arab, Sudanese Flzlani) populations. The respective frequencies of alleles a sl-Cn B and a sl-Cn c in the N'Dama (0.89 and 0.11) and Baoulé (0.92 and 0.08) breeds were almost opposite to those found in the Shuwa Arab zebu (0.22 and 0.78), a true zebu, which confirms a phenomenon already documented in the literature. Because the a sl-Cn B , / 3-Cn Al , Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
38
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 13 publications
13
38
1
1
Order By: Relevance
“…The observation that casein haplotype frequencies are geographically distributed is in accordance to the findings of former studies based on protein polymorphism [7,23,28]. Mahé et al [28] described the predominance of a haplotype on the basis of three casein genes CSN1S1*C-CSN2*A 2 -CSN3*A in zebu breeds.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The observation that casein haplotype frequencies are geographically distributed is in accordance to the findings of former studies based on protein polymorphism [7,23,28]. Mahé et al [28] described the predominance of a haplotype on the basis of three casein genes CSN1S1*C-CSN2*A 2 -CSN3*A in zebu breeds.…”
Section: Discussionsupporting
confidence: 85%
“…Mahé et al [28] described the predominance of a haplotype on the basis of three casein genes CSN1S1*C-CSN2*A 2 -CSN3*A in zebu breeds. However, the electrophoretic methods they used does not allow the discrimination between CSN3*H and CSN3*A I from CSN3*A. Consequently, the occurrence of haplotypes CA 2 A I and CA 2 H, which are within BCA 2 AA I , CCA 2 AA I , BCA 2 AH, and CCA 2 AH, is in agreement with these findings and indicates the introgression of Bos indicus in southern and eastern European cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been undertaken on a broad scale to encompass populations not only from different regions of the globe but also at a local level among closely related populations within particular regions [4,18,22,30,33,38]. Manwell and Baker [31] were the first to present a phylogenetic tree for the ten major cattle breed-groups of Europe, Western Asia, and Northern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…MacHugh et al [25] in a study on cattle breeds from Africa, Europe and India reported the highest diversity levels in African Bos indicus breeds, which are comparable to diversity levels at a center of origin [22]. The admixed nature of African Bos indicus breeds is thought to be responsible for its increased level of diversity [26]. It is therefore necessary to assess diversity levels in more breeds in the region in order to determine improvement and conservation priorities.…”
Section: Introductionmentioning
confidence: 99%